Molecular Identification of Necrophagous Muscidae and Sarcophagidae Fly Species Collected in Korea by Mitochondrial Cytochrome c Oxidase Subunit I Nucleotide Sequences - Yu-Hoon Kim; Sang Eon Shin; Chan Seon Ham; Seong Yoon Kim; Kwang Soo Ko; Tae-Ho Jo; Gi Hoon Son; Seong Hwan Park; Juck-Joon Hwang (The Scientific World Journal)
Identification of insect species is an important task in forensic entomology. For more convenient species identification, the nucleotide sequences of cytochrome c oxidase subunit I (COI) gene have been widely utilized. We analyzed full-length COI nucleotide sequences of 10 Muscidae and 6 Sarcophagidae fly species collected in Korea. After DNA extraction from collected flies, PCR amplification and automatic sequencing of the whole COI sequence were performed. Obtained sequences were analyzed for a phylogenetic tree and a distance matrix. Our data showed very low intraspecific sequence distances and species-level monophylies. However, sequence comparison with previously reported sequences revealed a few inconsistencies or paraphylies requiring further investigation. To the best of our knowledge, this study is the first report of COI nucleotide sequences from Hydrotaea occulta, Muscina angustifrons, Muscina pascuorum, Ophyra leucostoma, Sarcophaga haemorrhoidalis, Sarcophaga harpax, and Phaonia aureola.